Pemanfaat Video Edukasi “Video Petunjuk Jalan SMK Negeri 1 Ciomas” pada warga Bogor - Annory Langga’o; Valianty Sariswara (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Bogor Regency is located in West Java, has 40 sub-districts covering 416 villages and 19 urban villages. One of the sub-districts in Bogor Regency is Ciomas District. Ciomas is 3 km from the zero point of Bogor which is located in front of City Hall, making Ciomas the only sub-district that is most strategic and closest to the city center compared to other sub-districts. One of the Vocational High Schools (SMK) located in Ciomas is SMK Negeri 1 Ciomas. SMK Negeri 1 Ciomas is the only superior school in the area with the status of a public school. One of the problems in this sub-district is traffic jams due to the large number of public transportation (angkot) and Ciomas itself is the smallest and most densely populated sub-district in Bogor Regency. This study aims to test the effectiveness of media in providing location reference directions to residents of Bogor Regency and Bogor City. The study used a quantitative approach with a pre-test and post-test method, with the media used in the form of video. The research produced a video instrument titled "Video of Directions to SMK Negeri 1 Ciomas." The results showed a change in respondents' attitudes after watching the video